Peran Lazismu Kota Parepare Dalam Penyaluran Dana Infaq Untuk Pemberdayaan Usaha Kecil - Andi Kiki Patmawati; Ramli Ramli; Muhammad Haramain (Jurnal Kajian Manajemen Dakwah, 2021)
The research focuses on the role of LAZISMU Parepare in disbursing infaq funds for small business empowerment, the research objective is to determine the role of LAZISMU Parepare in distributing infaq funds for small business empowerment and the impact of the distribution of infaq funds on small business empowerment. This research use desciptive qualitative approach. The data analysis technique used is both inductive. To test the validity of the data through triangulation, the triangulation used in this research is data triangulation, method and theory triangulation. The results showed that the distribution of infaq funds for empowerment that had been carried out by LAZISMU was very felt and beneficial for small businesses